1995
DOI: 10.1007/bf02254214
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal erythropoietin treatment of children with chronic renal failure

Abstract: Intraperitoneal erythropoietin was given to three children on chronic peritoneal dialysis. Doses between 100 and 150 units/kg were given undiluted into a dry cavity twice weekly and left for 10-12 h before resuming dialysis. Satisfactory haemoglobin levels were seen over a 6-month period and there were no complications. Intraperitoneal administration of erythropoietin is cost-effective and avoids the local pain of subcutaneous injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…While virtually all PD patients receive epoetin alfa subcutaneously (SC), numerous studies have examined the pharmacokinetics and efficacy of intraperitoneal (IP) administration of this drug (2)(3)(4)(5)(6). Recent data suggest IP dosing can lead to adequate drug absorption and efficacy if epoetin alfa is administered into an empty peritoneal cavity (3,(7)(8)(9)(10). Comparison of SC and IP administration of equivalent doses of epoetin alfa has revealed that similar peak plasma concentrations of the drug are achieved if the IP dose is instilled into a "dry" peritoneum for 4 hours (3).…”
Section: ♦ ♦ ♦ ♦ ♦ Conclusionmentioning
confidence: 99%
“…While virtually all PD patients receive epoetin alfa subcutaneously (SC), numerous studies have examined the pharmacokinetics and efficacy of intraperitoneal (IP) administration of this drug (2)(3)(4)(5)(6). Recent data suggest IP dosing can lead to adequate drug absorption and efficacy if epoetin alfa is administered into an empty peritoneal cavity (3,(7)(8)(9)(10). Comparison of SC and IP administration of equivalent doses of epoetin alfa has revealed that similar peak plasma concentrations of the drug are achieved if the IP dose is instilled into a "dry" peritoneum for 4 hours (3).…”
Section: ♦ ♦ ♦ ♦ ♦ Conclusionmentioning
confidence: 99%